THE INFLUENCE OF COMMUNICATION AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. CHANG HONG YIN HUA - Achmad Rozi; Imat Hikmat (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2021)
The purpose of this study was to determine whether communication and leadership style affect employee performance at PT. Chang Hong Yin Hua. The sample used in this study was a saturated sample of 30 people. Based on the results of the partial test for the Communication Variable (X1) tcount = 2.239 greater than ttable = 2.052, it can be concluded that Ho is rejected and Ha is accepted, so that Hypothesis 1 has been proven that there is a significant effect on Communication (X1) on Employee Performance (Y) . Meanwhile, based on the results of the partial test of the Leadership Style Variable (X2) tcount = 2.489 greater than ttable = 2.052, it can be concluded that Ho is rejected and Ha is accepted, so that Hypothesis 2 has been proven that there is a significant effect of Leadership Style (X2) on employee performance (Y )., while based on the results of the ANOVA test (F test) the value of Fcount = 8.504 is greater than the value of Ftable = 3.34 and Sig. (p) = 0.001. Where p < 0.05 Ho: rejected and Ha: accepted. Therefore, Hypothesis 3 has been proven that there is an effect of Communication (X1) and Leadership Style (X2) simultaneously on Employee Performance (Y). Finally, it can be seen that the Employee Performance of PT. Chang Hong Yin Hua is influenced by Communication and Leadership Style by 38.6%. While the remaining 61.4% is influenced by other factors that are thought to be indications that are not included in this study Keywords: Communication, Leadership Style and Performance